University reform and intellectual freedom - Valdecantos Alcaide, Antonio (Avances en Supervisión Educativa, 2009)
The university reforms undertaken after the 1999 Bologna Declaration do not constitute a strictly academic phenomenon, but also a social reform at a high level, that affects the concept itself of society and the role of intellectual freedom in the whole Freedom System of the liberal thought and ideology. Contrary to the basics of this tradition, it is maintained that the intellectual sphere must be included in the economic sphere and that institutions in which intellectual freedom could be practised must be considered -even with a certain amount of independence- as a part of the market. The purpose of this article is to show that present university reform is against what has been the usual way of constructing the idea of society from the 18th century onwards.